Top-Ten Pitfalls in Rotator Cuff Ultrasound - Griffith, James F. (Seminars in Musculoskeletal Radiology, 2019)
Shoulder ultrasound is a commonly performed imaging study that can accurately determine the presence of rotator cuff tendinosis and tears, as well as subacromial-subdeltoid bursal and long head of biceps tendon pathology. High accuracy depends on an awareness of imaging pitfalls that can be encountered and lead to over- or underdiagnosis of rotator cuff pathology. Ten common pitfalls of rotator cuff ultrasound scanning are presented along with ways to avoid these pitfalls.
Keywords: ultrasound; tendon; bursa; biceps tendon; rotator cuff